Improving environmental performance in shipping - Brynolf, Selma; Lindgren, Fredrik; Andersson, Karin; Wilewska-Bien, Magda; Baldi, Francesco; Granhag, Lena; Johnson, Hannes; Linné, Philip; Svensson, Erik; Zetterdahl, Maria (2016)
This book addresses the environmental issues related to shipping and the natural environment, including descriptions of and proposed solutions to the issues. Currently, challenges exist that must be addressed if shipping is to become sustainable and fulfil the zero vision of no harmful emissions to the environment. In this chapter, we evaluate the steps that have been taken (if any) to limit the various environmental issues and discuss possible steps to be taken to improve environmental performance. Furthermore, future challenges must also be addressed, e.g., the current trend o f increasing ship operations in the Arctic. In general, three factors could be addressed in order to reach environmentally sustainable shipping: regulations, technical solutions, and increased environmental awareness.